ANALISIS PENGEMBANGAN MODEL HUTAN TANAMAN INDUSTRI POLA MOSAIK DENGAN PENDEKATAN PROGRAM LINIER : Suatu Gagasan Pendekatan untuk Daerah Padang Lawas, Sumatera Utara - B D Nasendi; Hasanudin Hasanudin; lwan Nugroho; Mulyaningrum Mulyaningrum; O K Karyono; Tryono Tryono; Abdul Murod; Walpen Sipayung (Jurnal Penelitian Hasil Hutan, 1996)
A Study of Industrial Plantation Forest model in Padang Lawas, North Sumatera using new concept of HTI (HTI - Mozaic) as HTI - Mix cropping or HTI - agroforestry, as it is not only for wood production but also for agriculture (Horticulture Crop) and grass for cattle was conducted.Optimal solution using Linear Programming approach shows that plant composition ofIndustrial Plantation Forest-Mozaic development in Padang Lawas area are; shorea (10000 ha ), albizia (6914 ha), akasia (9375 ha), palm oil (4757 ha), king grass and brachiaria (2499 ha ). Shorea has a highest shadow price and critical constraint, so the increase in land allocation for shorea will be profitable. Furthermore, post-optimal analysis indicates that land area for shorea is increased double, profit will also increase about Rp 49,361 billions. While for other commodities solutions are relatively stable.